Adsorpsi Ion Pb2+ Dalam Air dengan Serbuk Ijuk Menggunakan Metode Langmuir & Freundlich - Abubakar Tuhuloula (Universitas Lambung Mangkurat, 2007)
- The tree of sugar palm (arengan pinata) what is at bar shares there are typical fibre of chromatic of is called black fibre of palmtree have the ability to absorb the metal ion that contaminating water. Ability of fibre of palmtree fasten the metal anticipated by caused by his is lignine content, which contain a lot of electron donor on it cell wall. Lignine interaction with the metal ion can be in the form of the ion exchange, adsorption or chelat.This research purpose besides to increase energy of adsorptivity fibre of palmtree, also determine the optimum condition of adsorption for 1 gram fibre of palmtree that is balance time with the variation of time submersion to 1 – 12 hours and optimum pH with the range between 4 – 7. Pattern of Adsorption fibre of palmtree to plumbun (lead) ion of pursuant to Langmuir or Freundlich method will be able to be determined by after done by variation of concentration at optimum condition.Measurement conducted by using Atomic Absorbance Separations (AAS). Optimum condition obtained by that is time submersion to 4 hour with the amount of plumbun (lead) adsorbate as much 5.93 ppm and optimum pH 7. With the variation concentration at this condition, adsorptivity fasten along with increasing it concentration. Pattern adsorption tend to follow the Freundlich method of because value mark with the square lines (R2) linear curve is almost 1 that is 0,9849 whereas for the curve of Langmuir method only 0,2811